KEMAMPUAN MENULIS PANTUN SISWA KELAS VII SMP YLPI MARPOYAN PROGRAM PLUS PEKANBARU - Saputra, Dedy; Hakim, Nursal; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research entitled a study on the ability of writing pantun in the first year student’s of SMP YLPI Marpoyan Program Plus Pekanbaru. The problems in this research is ability writing pantun suitably condition of pantun. This aimed to describe student ability in writing pantun on aspect about verse, ability writing pantun on aspect about total word and a part word, ability writing pantun on sampiran's aspect, and ability writing pantun on content aspect. Method utilized in this research it descriptive method. Data collecting tech that is done for research it utilizes tech essay. This research population as much 46 person and research sample also as much 46 person with sample establishment total. To analysis research data utilized by average formula by use of estimation criterion guidance. Analysis is research data is done to 191 pantun couplets. This research result most that identification (1 ) ability writing pantun on aspect about verse gets medium category with average 76,78, (2 ) ability wriing pantun on aspect about total word and a part word gets medium category with average 72,96, (3 ) ability writing pantun on sampiran's aspect gets medium category with average 77,83, and (4 ) ability writing pantun on content aspect gets medium category with average 80,96.Keyword: ability, writing, pantun